Water Transport Properties of Roots and Root Cortical Cells in Proton- and Al-Stressed Maize Varieties. - Gunse, B. (1997)
Root and root cell pressure-probe techniques were used to investigate the possible relationship between Al- or H+-induced alterations of the hydraulic conductivity of root cells (LPc) and whole-root water conductivity (LPr) in maize (Zea mays L.) plants. To distinguish between H+ and Al effects two varieties that differ in H+ and Al tolerance were assayed. Based on root elongation rates after 24 h in nutrient solution of pH 6.0, pH 4.5, or pH 4.5 plus 50 [mu]M Al, the variety Adour 250 was found to be H+-sensitive and Al-tolerant, whereas the variety BR 201 F was found to be H+-tolerant but Al-sensitive. No Al-induced decrease of root pressure and root cell turgor was observed in Al-sensitive BR 201 F, indicating that Al toxicity did not cause a general breakdown of membrane integrity and that ion pumping to the stele was maintained. Al reduced LPc more than LPr in Al-sensitive BR 201 F. Proton toxicity in Adour 250 affected LPr more than LPc. In this Al-tolerant variety LPc was increased by Al. Nevertheless, this positive effect on LPc did not render higher LPr values. In conclusion, there were no direct relationships between Al- or H+-induced decreases of LPr and the effects on LPc. To our knowledge, this is the first time that the influence of H+ and Al on root and root cell water relations has been directly measured by pressure-probe techniques.